Nonlinear strut-and-tie model with bond-slip effect for analysis of RC Beam-Column joints under lateral loading - Rattapon Ketiyot (2018)
© Int. J. of GEOMATE. This paper presents an application of nonlinear strut-and-tie model (NSTM) with bond-slip effect for analysis of reinforced concrete (RC) interior beam-column joints under lateral loading. The conventional STM is a calculation based on the force method exhibiting the internal forces in each component, it is unable to capture an inelastic response when RC beam-column joints undergo large displacement. Test results of three similar interior beam-column subassemblage frames with Grade400, Grade400s and Grade500 of longitudinal reinforcement bar, were used to verify the applicability of the NSTM, respectively. In the joint region, nonlinear links of concrete and steel bar with bond-slip effect were applied to simulate a load-displacement response. The results, such as maximum loading capacity, lateral load-story drift relation and failure mode, obtained from both NSTM models and laboratory experiments were compared. It was found that the results from the analyses using the NSTM with bondslip effect agreed well with the experimental results. Furthermore, the demand-to-capacity ratios of the nonlinear links, which represents the distribution of the internal force in the NSTMs' joint region, exhibit the failure location and the failure mode that compatible with the experimental result. Hence, the proposed model is capable of predicting the strength of interior beam-column joint of RC frames under lateral loading.